2020
DOI: 10.1136/medethics-2019-105961
|View full text |Cite
|
Sign up to set email alerts
|

Prepared for practice? UK Foundation doctors’ confidence in dealing with ethical issues in the workplace

Abstract: This paper investigates the medical law and ethics (MEL) learning needs of Foundation doctors (FYs) by means of a national survey developed in association with key stakeholders including the General Medical Council and Health Education England. Four hundred sevnty-nine doctors completed the survey. The average self-reported level of preparation in MEL was 63%. When asked to rate how confident they felt in approaching three cases of increasing ethical complexity, more FYs were fully confident in the more comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In such unprecedented times, it is unreasonable to assume that medical students-with no training or experience-would be equipped to handle such responsibility. 47 Mitigating the effects of such distress is vital for the prevention of adverse mental health outcomes. Therefore, appropriate pandemic preparedness should be structured as such.…”
Section: Student Essaymentioning
confidence: 99%
“…In such unprecedented times, it is unreasonable to assume that medical students-with no training or experience-would be equipped to handle such responsibility. 47 Mitigating the effects of such distress is vital for the prevention of adverse mental health outcomes. Therefore, appropriate pandemic preparedness should be structured as such.…”
Section: Student Essaymentioning
confidence: 99%
“…However, simply providing further teaching is insufficient in tackling the challenges identified in our study. On the contrary, we have previously identified that FDs' confidence for dealing with ethical issues in the workplace was unrelated to their ethics teaching received at medical school (Corfield et al 2020). Furthermore, it has been argued that teaching about whistleblowing without providing the supportive work environment for it to occur in can negatively impact FDs by causing moral distress (Martinez et al 2017).…”
Section: What Changes Can We Make?mentioning
confidence: 90%